2011
DOI: 10.1021/ci100458f
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinities of Factor Xa Inhibitors Estimated by Thermodynamic Integration and MM/GBSA

Abstract: We present free energy estimates of nine 3-amidinobenzyl-1H-indole-2-carboxamide inhibitors of factor Xa. Using alchemical thermodynamic integration (TI) calculations, we estimate the difference in binding free energies with high accuracy and precision, except for mutations involving one of the amidinobenzyl rings. Crystal studies show that the inhibitors may bind in two distinct conformations and using TI, we show that the two conformations give a similar binding affinity. Furthermore we show that we can redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
167
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 74 publications
(173 citation statements)
references
References 55 publications
4
167
0
Order By: Relevance
“…First, the MM free energies were based on 13 rather than three  values. Three  values have been shown to be enough in a previous investigation, giving errors of less than 2 kJ/mol [91]. However, this of course depends on the specific transformations.…”
Section: Fep Results At the Dft-d3 Levelmentioning
confidence: 88%
“…First, the MM free energies were based on 13 rather than three  values. Three  values have been shown to be enough in a previous investigation, giving errors of less than 2 kJ/mol [91]. However, this of course depends on the specific transformations.…”
Section: Fep Results At the Dft-d3 Levelmentioning
confidence: 88%
“…Previously, we have analysed how many unphysical intermediate states and how long simulation are needed to obtain accurate results. 8 We showed that for our test case, rather few intermediate states (3 to 5) were enough and the simulation time should be ~1 ns for the protein-ligand simulations and 2 ns for the free ligand simulations.…”
Section: Introductionmentioning
confidence: 77%
“…Previously, we have analysed how many unphysical intermediate states and how long simulation are needed to obtain accurate results. 8 We showed that for our test case, rather few intermediate states (3 to 5) were enough and the simulation time should be ~1 ns for the protein-ligand simulations and 2 ns for the free ligand simulations.Apart from improvements in the simulation protocol, the system itself can be changed in a way that reduces the computer requirements. One approach that has been used by some research groups for the calculation of protein-ligand affinities is to simulate only a part of the protein, immersed in a droplet of explicit water molecules.…”
mentioning
confidence: 77%
“…These systems have been used in previous studies of free energy methods. 15,16,17 MD simulations. The MD simulations of the fXa and ferritin complexes were conducted by the Amber10 software 32 and they were taken from previous studies.…”
Section: δG Bind = G(pl) -G(p) -G(l)mentioning
confidence: 99%
“…These systems have been used in previous studies of free energy methods. 15,16,17 Methods Preparation of proteins and ligands. In this paper, we study eight 3-amidinobenzyl-1H-indole-2-carboxamide inhibitors of fXa, 18 nine inhibitors to ferritin, as well as the two inhibitors amprenavir (APV) and darunavir (DRV) binding to either wild-type (WT) or a double mutant (V82T/I84V, MT) HIV-1 protease (HIV-PR).…”
mentioning
confidence: 99%